Holistic Education: Shaping Students' Strong Character and Emotional Intelligence to Face Global Challenges - Puniman, Ach. (LP2M IAI Al-Khairat Pamekasan, 2023)
Holistic education is a strategic approach to shaping students who excel not only academically but also in character and emotional intelligence. This approach integrates the development of cognitive, emotional, social, and spiritual aspects, all of which are essential to navigating the increasingly complex global challenges. This study employs a qualitative approach with a descriptive method to explore the implementation of holistic education in Indonesian schools. The findings indicate that holistic education effectively fosters students' integrity, empathy, and critical thinking skills. However, its implementation faces various challenges, such as limited understanding of holistic concepts, resource constraints, and academic pressure. Therefore, collaboration among schools, teachers, parents, and the community is essential to creating an educational ecosystem that supports holistic approaches. Holistic education is expected to be a long-term solution in building a globally competitive, morally grounded, and socially contributive generation.